The Design Of Web-Based Thesis Management Data Information System - Muhammad Nang Al Kodri (INTECH, 2024)
Web-based information systems have developed significantly over the last few years with their improvements. An information system that can facilitate service, and access to get information and data management. So that better service to students will be obtained. This research can help students and informatics study programs in archiving thesis data. The research method in this study is a. Observation Method, observation by directly observing the campus environment of the Baturaja University Informatics Study Program to obtain information about the fluidity of the current system used to produce information systems; b. Library Study Method Literature study technique is by collecting data and information on written materials related to the discussion of problems in this study, c. Interview method and d. the information system development method in this study uses the Rapid Application Development or RAD model. Based on the results and discussion in this study, the authors conclude that the creation of a Web-Based Thesis Data Information System at Baturaja University The process of collecting thesis files in the form of softcopy is no longer done conventionally, namely thesis files just need to be uploaded through the system and thesis searches can be done easily online.